2000
DOI: 10.1046/j.1365-2427.2000.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in density, mean size and physiological condition of the holarctic amphipod Diporeia spp. in Lake Michigan

Abstract: Summary We examined spatial patterns in population characteristics (density, biomass, mean body length) and physiological condition (lipid content, length‐weight) of the amphipod Diporeia spp. in Lake Michigan by collecting samples at up to 85 sites in late summer 1994 and 1995. Variables were examined relative to water depth and three lake regions: south, central and north. Most major river systems are found in the south, and this region is more nutrient‐enriched compared to the north. Over all sites, mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…Prey items were removed from stomachs (from esophagus to pyloric caeca), categorized into common prey groups (Table 1), and counted. Lengths of prey items were measured and converted to dry weight using length-weight regressions (Nalepa and Quigley, 1980;Rosen, 1981;Shea and Makarewicz, 1989;Basset and Glazier, 1995;Nalepa et al, 2000). The dry weight of partially digested prey items was assumed to be equal to the mean weight of measured whole prey items.…”
Section: Methodsmentioning
confidence: 99%
“…Prey items were removed from stomachs (from esophagus to pyloric caeca), categorized into common prey groups (Table 1), and counted. Lengths of prey items were measured and converted to dry weight using length-weight regressions (Nalepa and Quigley, 1980;Rosen, 1981;Shea and Makarewicz, 1989;Basset and Glazier, 1995;Nalepa et al, 2000). The dry weight of partially digested prey items was assumed to be equal to the mean weight of measured whole prey items.…”
Section: Methodsmentioning
confidence: 99%
“…Diporeia has historically been the most abundant benthic invertebrate in the offshore water (N30 m) of the Great Lakes. Its life history information is less well described for Lake Superior than for the other Great Lakes (Eggleton 1937;Winnell and White 1984;Nalepa et al 2000;Dermott 2001;Guiguer and Barton 2002). The amphipod phylogroup Diporeia has been the subject of much study because of their critical link to the fishery and their recent precipitous decline in all of the Great Lakes except Lake Superior.…”
Section: Introductionmentioning
confidence: 99%
“…Diporeia have been found to be more densely distributed on the slope (rapid drop between shelf and profundal habitats) compared to the shelf (wave-dominated sandy shoreline areas) and profundal (somewhat level lake bottom regions) regions of the Great Lakes (Auer and Kahn 2004;Evans et al 1990), with density maxima observed at depths of 40 to 80 m (Auer and Kahn 2004;Cook 1975 andKraft 1979) in Lake Superior. Peaks in Diporeia abundance were reported at 40 to 60 m in Lake Michigan (Eggleton 1937;Mozley and Alley 1973;Nalepa et al 2000;Robertson and Alley 1966) and at 30 to 39 m in Lake Ontario (Sly and Christie 1992).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the decline in Diporeia spp. may be due to the nonindigenous zebra mussel D. polymorpha intercepting the algal diet before it settles to the bottom, thus decreasing the amount available to these amphipods (Nalepa et al 1998(Nalepa et al , 2000. However, sampling efforts indicate that sufficient food is still available to support the benthic amphipod populations, and that lipid content and body condition (weight per unit length) of Diporeia spp.…”
Section: Introductionmentioning
confidence: 99%